“Thy physic I will try”: Art, Nature, and Female Healing in Shakespeare - Zamparo, Martina (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2022)
As one reads in Aristotle’s Physics, art both imitates and completes nature, being not only a ministra naturae but also a ‘corrector’ of nature. Through the major influence of Paracelsianism, in Shakespeare’s England the art of medicine was closely associated with alchemy. The latter, as William Newman has noted, “provided a uniquely powerful focus for discussing the boundary between art and nature”. By considering the characters of Marina (Pericles; Prince of Tyre) and Helen (All’s Well That Ends Well), this essay investigates the two women’s relation to the healing arts and to nature in the light of coeval alchemical and Paracelsian doctrines. The two Shakespearean women employ their healing powers, i.e. their “artificial feat”, as well as their knowledge of nature’s occult sympathies and antipathies, in the service of a “kingly patient”: Pericles and the King of France. The topos of the healing of the king is a common trope in Renaissance alchemical literature, where the ‘king’ represents gold in potentia and, thus, the raw matter that has to be purified by Lady Alchymya. In the light of their privileged access to nature’s secret workings, women could manipulate nature and heal the human body. The analysis will focus on Marina’s homeopathic and, therefore, Paracelsian healing of her father Pericles and on Helen’s still controversial medical practice, which seems to exceed both the Galenic and the Paracelsian paradigm.